Narrative Based Medicine as a tool for needs assessment of patients undergoing hematopoietic stem cell transplantation - Gargiulo, Gianpaolo; Sansone, Vincenza; Rea, Teresa; Artioli, Giovanna; Botti, Stefano; Continisio, Grazia Isabella; Ferri, Paola; Masi, Daniela; Risitano, Antonio Maria; Simeone, Silvio; La Sala, Rachele (Acta Biomedica Atenei Parmensis, 2017)
Background and aim: In the last years we have seen an ever increasing number of patients with haematologic disorders who need hematopoietic stem cell transplantation (HSCT). The whole sector of HSCT results, infact to be in a continous scientific and technological clinical progress, offering a very advanced care. Despite this, some aspects are underconsidered, some of which could be fundamental to determine the success of the care pathway, such as the experience of the illness by the patient. Using a Narrative Based Medicine approach we wanted to investigate clinical, psychosocial and organizational aspects of the patient’s journey whilst undergoing HSCT. Method: Various narrative interviews were conducted using non-structured approach. Results were analysed by thematic contents. Results: Psycological dimension is the most compromised: above all emerged sentiments of oppression linked to the isolation period in the Low Bacterial Load (LBL) room. To note are also the different dynamics with which the patients perceive the organisation and hospital structures, and how much these factors can influence their care experience. Conclusions: Results suggest the need in clinical practice of an integration between qualitative and clinical approach, so as to permit the psychosocial and relational necessities to emerge, often unexpressed by patients undergoing HSCT.